The learning innovation of art performance development courses of PGSD students' in UNP Kediri in calon arang story - Wahyudi; Rukmana Sari, Ayu; Titis Rukmana Sari, Ayu (Universitas Nusantara PGRI Kediri, 2022)
This study primarily conducted to find out the learning innovation of art performance development of PGSD students of UNP Kediri in Calon Arang story. This article is the result of qualitative study by art performance approach, by using ethnography method, by focusing on art performance creator which is the students. The data collected were gained by doing an observation, interview, a literature research, and document study. The learning goal of art performance at campus is not only interpreted as creating the students to be the actors, but also focused on developing skill potential and knowledge, and processing students creativity in creating art performance.